2013
DOI: 10.1002/syn.21643
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of [18F]MH.MZ and [18F]altanserin for 5‐HT2A receptor imaging with PET

Abstract: Imaging the cerebral serotonin 2A (5-HT2A ) receptors with positron emission tomography (PET) has been carried out in humans with [(11) C]MDL 100907 and [(18) F]altanserin. Recently, the MDL 100907 analogue [(18) F]MH.MZ was developed combining the selectivity profile of MDL 100907 and the favourable radiophysical properties of fluorine-18. Here, we present a direct comparison of [(18) F]altanserin and [(18) F]MH.MZ. 5-HT2A receptor binding in pig cortex and cerebellum was investigated by autoradiography with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…11 This can be attributed to a relatively high concentration of 5-HT 2A receptors in the pig cerebellum which was also recently described. 31 In summary, we have shown that the novel receptor agonist PET radioligand, …”
Section: Resultsmentioning
confidence: 87%
“…11 This can be attributed to a relatively high concentration of 5-HT 2A receptors in the pig cerebellum which was also recently described. 31 In summary, we have shown that the novel receptor agonist PET radioligand, …”
Section: Resultsmentioning
confidence: 87%
“…Two groups reported [ 18 F]fluoroethyl-M100907 ([ 18 F]FEM100907 aka [ 18 F]MH.MZ), a fluoroethyl analogue of M100907 with faster off-rate than [ 11 C]M100907 [110,111]. [ 18 F]MH.MZ has higher cortex to cerebellum ratio in nonhuman primates and pigs [112]. Further studies are required to establish the utility of [ 18 F]MH.MZ in human studies.…”
Section: Introductionmentioning
confidence: 99%
“…To test whether this is the case, a displacement study with the known 5‐HT 2A R antagonist ketanserin was conducted. The experimental setup used within this study has previously been successfully applied in the same animal model for [ 11 C]Cimbi‐36 or [ 18 F]MH.MZ . The displacement study was performed after 90 minutes.…”
Section: Resultsmentioning
confidence: 99%